Researches on cognitive sequelae of burn injury: Current status and advances - Xie, Chenchen; Hu, Jun; Cheng, Yong; Yao, Zhongxiang (Frontiers in Neuroscience, 2022)
Burn injury is a devastating disease with high incidence of disability and mortality. The cognitive dysfunctions, such as memory defect, are the main neurological sequelae influencing the life quality of burn-injured patients. The post-burn cognitive dysfunctions are related to the primary peripheral factors and the secondary cerebral inflammation, resulting in the destruction of blood-brain barrier (BBB), as is shown on Computed Tomography (CT) and magnetic resonance imaging examinations. As part of the neurovascular unit, BBB is vital to the nutrition and homeostasis of the central nervous system (CNS) and undergoes myriad alterations after burn injury, causing post-burn cognitive defects. The diagnosis and treatment of cognitive dysfunctions as burn injury sequelae are of great importance. In this review, we address the major manifestations and interventions of post-burn cognitive defects, as well as the mechanisms involved in memory defect, including neuroinflammation, destruction of BBB, and hormone imbalance.